Thermoresponsive Magnetic Hydrogels as Theranostic Nanoconstructs - Jaiswal, Manish K. (American Chemical Society, 2014)
[Image: see text] We report the development of thermoresponsive magnetic hydrogels based on poly(N-isopropylacrylamide) encapsulation of Fe(3)O(4) magnetic nanostructures (MNS). In particular, we examined the effects of hydrogels encapsulated with poly-ethylene glycol (PEG) and polyhedral oligomeric silsesquioxane (POSS) surface modified Fe(3)O(4) MNS on magnetic resonance (MR) T(2) (transverse spin relaxation) contrast enhancement and associated delivery efficacy of absorbed therapeutic cargo. The microstructural characterization reveal the regular spherical shape and size (∼200 nm) of the hydrogels with elevated hydrophilic to hydrophobic transition temperature (∼40 °C) characterized by LCST (lower critical solution temperature) due to the presence of encapsulated MNS. The hydrogel-MNS (HGMNS) system encapsulated with PEG functionalized Fe(3)O(4) of 12 nm size (HGMNS-PEG-12) exhibited relaxivity rate (r(2)) of 173 mM(–1)s(–1) compared to 129 mM(–1)s(–1) obtained for hydrogel-MNS system encapsulated with POSS functionalized Fe(3)O(4) (HGMNS-POSS-12) of the same size. Further studies with HGMNS-PEG-12 with absorbed drug doxorubicin (DOX) reveals approximately two-fold enhance in release during 1 h RF (radio-frequency) field exposure followed by 24 h incubation at 37 °C. Quantitatively, it is 2.1 μg mg(–1) (DOX/HGMNS) DOX release with RF exposure while only 0.9 μg mg(–1) release without RF exposure for the same period of incubation. Such enhanced release of therapeutic cargo is attributed to micro-environmental heating in the surroundings of MNS as well as magneto-mechanical vibrations under high frequency RF inside hydrogels. Similarly, RF-induced in vitro localized drug delivery studies with HeLa cell lines for HGMNS-PEG-12 resulted in more than 80% cell death with RF field exposures for 1 h. We therefore believe that magnetic hydrogel system has in vivo theranostic potential given high MR contrast enhancement from encapsulated MNS and RF-induced localized therapeutic delivery in one nanoconstruct.